Pengaruh Model Discovery Learning Terhadap Aktivitas dan Hasil Belajar Kognitif Peserta Didik - Oktriviani, Shella Oktriviani; Marpaung, Rini Rita; Yolida, Berti Yolida (Jurnal Pendidikan MIPA, 2017)
The Effect of Discovery Learning Models on Activities and Students Cognitive Learning Outcomes. This study aims to determine the effect of discovery learning on activities and cognitive learning outcomes students of class VIII SMPN 1 Lawang Kidul in "Human Blood Circulation System" materials. The study sample were32 students of class VIII that were selected by cluster random sampling technique. The research instrument used a sheet of pretest-posttest and observation sheet of student activities. The design used was nonequivalent pretest-posttest control group design. Data on activities were analyzed descriptively, while pretest-posttest and n-Gain values were analyzed by Independent Sample t-test. The results of the study showed that the average percentage activity was 74.2 with good criteria with N-Gain average that was 0.66 with medium criteria. Thus the application of the discovery learning model has a significant effect on the activities and cognitive learning outcomes of students in "Human Blood Circulation” materials.Keywords: activities, discovery learning, learning outcomes, human blood circulationsystem DOI: http://dx.doi.org/10.23960/jpmipa/v18i2.pp51-59